Preparation method and application of rare earth-manganese composite amorphous catalyst for catalyzing VOCs (Volatile Organic Compounds)

Through the rare earth-doped amorphous manganese-based catalyst preparation method, the problem of poor activity of VOCs catalysts at low temperatures is solved, efficient VOCs conversion and CO2 yield are achieved, and a low-cost and high-performance catalyst solution is provided.

CN119236918AActive Publication Date: 2025-01-03BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411322205.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing VOCs catalysts have poor activity under low temperature conditions, low degree of deep oxidation, and it is difficult to effectively purify volatile organic matter. The synthesis of transition metal oxides is simple but costly.

Method used

Using rare earth doped high-performance amorphous manganese-based catalyst preparation method, the pH value is adjusted, and potassium permanganate solution is added to conduct hydrothermal reaction by magnetic stirring of Mn(CH3COO)2·4H2O and rare earth element precursor in deionized water. , an amorphous rare earth-manganese composite catalyst is formed, and a catalyst with high specific surface area and abundant oxygen defects is obtained by calcining and grinding.

Benefits of technology

Under 200°C, the catalyst can achieve 100% VOCs conversion rate and 90% CO2 yield, which significantly improves low-temperature activity. It has better performance than pure MnO2 catalysts, and is simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236918A_ABST
    Figure CN119236918A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a rare earth-manganese composite amorphous catalyst for catalyzing VOCs (Volatile Organic Compounds). The method comprises the following steps: uniformly mixing a rare earth element (Ce, La, Pr and Nd) precursor with manganese acetate, and adjusting the pH value of the solution to be 4.0-6.5 or 7.2-8.0; dropwise adding a potassium permanganate solution, and transferring the obtained mixed solution into a hydrothermal reaction kettle to react for 16 hours at 100 DEG C; and collecting a black precipitate, washing, drying, roasting and grinding to obtain the rare earth-manganese composite amorphous catalyst. According to the preparation method, MnO2 lattice expansion is caused by doping rare earth elements with large ion radiuses, so that a tunnel structure collapses, grain agglomeration and crystal growth rate are delayed by adjusting pH and temperature, and the rare earth-manganese composite amorphous catalyst is obtained. The catalyst has a larger specific surface area, abundant defect sites and a uniform active center, shows excellent VOCs catalytic activity, and is simple to operate and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of VOCs catalyst preparation, and in particular to the preparation of a rare earth-doped high-performance amorphous manganese-based catalyst and its application in catalytic purification of VOCs. Background Art

[0002] Currently, volatile organic compounds (VOCs) are used as precursors to participate in a series of chemical reactions to generate secondary pollutants (O3 and PM 2.5 ) is still the main atmospheric environmental problem faced by most parts of my country. It is of various types and wide sources, and the governance situation is urgent. Catalytic oxidation is currently one of the most effective methods for terminal control of VOCs. Many scholars at home and abroad have invested a lot of research on the exploration of catalysts. Compared with precious metals, transition metal oxides are inexpensive and easy to synthesize. They also have good oxygen storage capacity and have attracted much attention in the catalytic reaction of VOCs. However, there are still problems such as poor low-temperature activity and low degree of deep oxidation. Therefore, it is very important to develop new catalytic materials that can efficiently catalyze and purify VOCs under mild conditions.

[0003] There are many strategies for catalyst development, such as adjusting the catalyst preparation method, constructing interfaces between different metals, Designing catalyst morphology and structure, etc. The oxygen defect concentration affects the escape energy of surface lattice oxygen and is an intrinsic factor that determines catalytic activity. Therefore, oxygen vacancy engineering is often used to optimize materials and improve catalytic performance. Metal doping can adjust the oxygen vacancy concentration by introducing other elements. If it can cause structural distortion to prepare amorphous materials, the surface atomic coordination of this long-range disordered and short-range ordered amorphous structure is highly unsaturated, which can produce more oxygen defects. At the same time, amorphous materials have the characteristics of small grain size, high specific surface area and porosity, which can promote the diffusion and confined enrichment of VOCs on the surface, and can further improve performance compared to highly crystalline catalytic materials.

[0004] MnO2 has rich structure and electronic properties Dynamically adjustable, the connection mode of [MnO6] octahedron determines the crystal morphology of MnO2. Rare earth elements with ion radius larger than Mn are easily doped to cause MnO2 lattice expansion and collapse of its tunnel structure. Therefore, by adjusting the catalyst ratio and preparation conditions, stable amorphous materials can be obtained within a wider control range, and the operation is simpler.

[0005] CN104001502B provides a method for preparing a cerium manganese catalyst for decomposing ozone, characterized in that a manganese source, a cerium source and potassium permanganate are mixed in a limited weak acid environment to obtain a catalyst with high crystallinity. CN108630457B uses potassium hydroxide as a precipitant and mixes it with a manganese source and potassium permanganate to prepare an amorphous manganese oxide for use as a positive electrode material for a battery, but its calcination temperature needs to be controlled at 400°C. Summary of the invention

[0006] One of the purposes of the present invention is to solve the problem of poor low-temperature activity of current VOCs catalysts, and to provide a method for preparing a rare earth-manganese composite binary amorphous catalyst for efficiently degrading VOCs.

[0007] To achieve the above object, the method is carried out according to the following steps:

[0008] (1) Mn(CH3COO)2·4H2O and rare earth element precursors are dissolved in deionized water, and magnetically stirred at 400 r / min until they are completely dissolved to form a mixed solution, and the pH is adjusted to 4.0-6.5 or 7.2-8.0.

[0009] (2) Add potassium permanganate solution to the solution in step (1), stir for 30 min, transfer the obtained brown liquid into a hydrothermal reaction kettle, and carry out hydrothermal reaction at 80-110° C. for 12-24 h.

[0010] (3) Washing, drying, calcining and grinding the precipitate obtained in step (2) to obtain an amorphous rare earth-manganese composite binary catalytic material.

[0011] The present invention adopts a simple hydrothermal synthesis method to obtain a series of rare earth-manganese binary catalysts with different compositions and different ratios, wherein the rare earth elements include Ce, La, Pr, Nd, and the molar ratio of the rare earth elements to manganese is 0.12-0.60. 0.24 Catalyst at space velocity 30000ml g -1 ·min -1 , chlorobenzene concentration 3000mg / m 3 Under the condition of 200℃, the conversion rate can reach 100%, and the CO2 yield is above 90%. Compared with pure MnO2, the activity is significantly improved.

[0012] The concentration of Mn(CH3COO)2·4H2O in step (1) is 0.425 mol / L.

[0013] In step (1), the rare earth element is Ce, La, Pr, Nd, and the precursor is selected from one of nitrate, acetate or chlorate. The mixed solution is, for example, a mixed solution of manganese acetate and cerium nitrate, a mixed solution of manganese acetate and cerium acetate, or a mixed solution of manganese acetate and cerium chloride.

[0014] The pH adjustment range in step (1) is 4.0 to 6.5 or 7.2 to 8.0. The pH is adjusted within the range of the absolute value of the zeta potential greater than 30, with the zero point charge (PZC) of the solution being 6.8. Acetic acid, hydrochloric acid, and nitric acid are used to adjust the pH with acid, and 0.1 mol / L sodium hydroxide solution is used to adjust the pH with alkali. Hydroxyl groups in weak acid and weak base environments interact with oxygen negative charge sites to form hydrogen bonds, which can improve the stability of the solution, retard grain agglomeration and crystal growth rate during the hydrothermal reaction, and help form a highly dispersed amorphous structure. Excessive acidity or alkali can cause the hydroxyl groups to deprotonate and reduce the stability of the solution, and a hydrolysis reaction of the precursor can be triggered in a strong base environment.

[0015] The concentration of the potassium permanganate solution in step (2) is 0.2-0.3 mol / L.

[0016] The hydrothermal reaction temperature in step (2) is 80-110° C., for example, 80° C., 90° C., 100° C., 110° C. If the hydrothermal reaction temperature is too low, the composite oxide bonding force is weak and the product yield is not high; if the hydrothermal reaction temperature is too high, MnO2 will be converted into Mn2O3, and the activity will decrease.

[0017] The hydrothermal reaction time in step (2) is 12 to 24 hours, for example 12 hours, 16 hours, 20 hours, 24 hours.

[0018] In step (3), anhydrous ethanol and deionized water are used for washing multiple times until the mixture becomes neutral.

[0019] The drying temperature in step (3) is 90-110° C., and the drying time is 12-24 hours.

[0020] The calcination conditions in step (3) are: in air atmosphere, the calcination temperature is 300-600°C, and the calcination time is 3-5 hours. If the temperature is too high, the amorphous phase will be transformed, and the main active component will change from MnO2 to Mn2O3, and the activity will be reduced.

[0021] The second purpose of the present invention is to provide a new method for oxygen defect engineering and catalyst morphology design. The amorphous catalytic material induced by rare earth element-Mn composite metal oxide has a smaller grain size and a larger specific surface area. The unique distorted lattice and the coexistence of multiple valence states make it have abundant surface defects and uniform active centers.

[0022] The rare earth-manganese composite amorphous catalyst synthesized by the above method has abundant structural defects, which can serve as sites for the adsorption and activation of reactant molecules. The dangling bonds and localized electrons on the surface can regulate the electronic state and oxygen species transfer process, and are the key to completing the entire chemical cycle.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The catalyst described in the present invention has an amorphous structure, and no obvious diffraction peaks corresponding to MnO2 and other rare earth oxides are observed in the X-ray diffraction spectrum, indicating that the catalyst has extremely low crystallinity, small microscopic size and good dispersibility. At the same time, the catalyst has a large specific surface area and porosity, which is conducive to the adsorption and diffusion of reaction molecules on the surface.

[0025] (2) The amorphous catalysts prepared by the present invention, which are composited with different rare earth elements and manganese, are heated at a space velocity of 30000 ml·g -1 ·min -1 , chlorobenzene concentration 3000mg / m 3 Under the conditions of , the conversion rate can reach 100% at 200℃, and the CO2 yield is above 90%. Compared with the manganese-based catalysts with clear crystal forms prepared by other methods, it has higher low-temperature activity. After the reaction, the catalyst is still amorphous and has good stability.

[0026] (3) The amorphous catalyst prepared by the present invention is simple to operate, low in cost, good in performance, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 CeMn a XRD results of the composite catalyst.

[0028] Figure 2 MnO2 and CeMn 0.24 SEM image of the catalyst.

[0029] Figure 3 MnO2 and CeMn 0.24 HRTEM image of the catalyst.

[0030] Figure 4 XMn 0.36 XRD patterns of the composite catalysts.

[0031] Figure 5 CeMn prepared from different cerium precursors 0.24 XRD patterns of the composite catalysts.

[0032] Figure 6 CeMn prepared under different pH conditions 0.24 XRD patterns of the composite catalysts.

[0033] Figure 7 CeMn prepared at different hydrothermal temperatures 0.24 XRD patterns of the composite catalysts.

[0034] Figure 8 CeMn prepared at different calcination temperatures 0.24XRD patterns of the composite catalysts.

[0035] Fig. 9 CeMn a VOCs catalytic activity diagram of the composite catalyst. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0037] Example 1

[0038] A method for preparing a cerium-manganese amorphous catalyst: 4.16g Mn(CH3COO)2·4H2O and 0.89g Ce(NO3)3·6H2O are dissolved in deionized water, magnetically stirred until the solid is completely dissolved to form a mixed solution, and 1.0ml acetic acid is added to adjust the pH to 4.5. 0.26mol / L KMnO4 solution is added to the above mixed solution and magnetically stirred for 30min at room temperature to mix it evenly. The mixed solution is then transferred into a 100ml hydrothermal reactor and reacted at 100°C for 16h. After cooling, the collected precipitate is alternately washed three times with anhydrous ethanol and deionized water until neutral, and placed in a 100°C oven to dry for 24h. The obtained solid is placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min in an air atmosphere for 4h. CeMn is obtained after grinding. 0.12 Amorphous catalyst.

[0039] Example 2

[0040] The amount of Ce(NO3)3·6H2O added in Example 1 was changed to 1.77 g, and the other operations were referred to Example 1 to obtain CeMn 0.24 Amorphous catalyst.

[0041] Example 3

[0042] The amount of Ce(NO3)3·6H2O added in Example 1 was changed to 2.65 g, and the other operations were referred to Example 1 to obtain CeMn 0.36 Amorphous catalyst.

[0043] Example 4

[0044] The amount of Ce(NO3)3·6H2O added in Example 1 was changed to 3.54 g, and the other operations were referred to Example 1 to obtain CeMn 0.48 Amorphous catalyst.

[0045] Example 5

[0046] The amount of Ce(NO3)3·6H2O added in Example 1 was changed to 4.43 g, and the other operations were referred to Example 1 to obtain CeMn 0.60Amorphous catalyst.

[0047] Example 6

[0048] The Ce(NO3)3·6H2O in Example 1 was replaced with La(NO3)3·6H2O, and the addition amount was 2.06 g. The other operations were referred to Example 1 to obtain LaMn 0.36 Amorphous catalyst.

[0049] Example 7

[0050] The Ce(NO3)3·6H2O in Example 1 was replaced with Pr(NO3)3·6H2O, and the addition amount was 2.61 g. The other operations were referred to Example 1 to obtain PrMn 0.36 Amorphous catalyst.

[0051] Example 8

[0052] The Ce(NO3)3·6H2O in Example 1 was replaced with Nd(NO3)3·6H2O, and the addition amount was 2.63 g. The other operations were referred to Example 1 to obtain NdMn 0.36 Amorphous catalyst.

[0053] Example 9

[0054] The Ce(NO3)3·6H2O in Example 1 was replaced by Ce(CH3COO)3·xH2O, and the addition amount was 1.27 g. The other operations were referred to Example 1 to obtain CeMn 0.24 -C amorphous catalyst.

[0055] Example 10

[0056] The Ce(NO3)3·6H2O in Example 1 was replaced by Ce(Cl)3·7H2O, and the addition amount was 1.49 g. The other operations were referred to Example 1 to obtain CeMn 0.24 -L Amorphous catalyst.

[0057] Embodiment 11

[0058] The amount of acetic acid added in Example 2 was changed to 0.1 ml, the pH was adjusted to 6, and the other operations were referred to Example 2 to obtain CeMn 0.24 -pH 6.0 amorphous catalyst.

[0059] Example 12

[0060] The amount of acetic acid added in Example 2 was changed to 3 ml, the pH was adjusted to 4, and the other operations were referred to Example 2 to obtain CeMn 0.24 -pH 4.0 amorphous catalyst.

[0061] Embodiment 13

[0062] The acetic acid in Example 2 was replaced with sodium hydroxide solution, and the pH was adjusted to 8.0. The other operations were carried out in accordance with Example 2 to obtain CeMn 0.24 -pH 8.0 amorphous catalyst.

[0063] Embodiment 14

[0064] The hydrothermal temperature in Example 2 was changed to 80°C, and the other operations were referred to Example 2 to obtain CeMn 0.24 -HT80 amorphous catalyst.

[0065] Embodiment 15

[0066] The hydrothermal temperature in Example 2 was changed to 110°C, and the other operations were referred to Example 2 to obtain CeMn 0.24 -HT110 amorphous catalyst.

[0067] Example 16

[0068] The calcination temperature in Example 2 was changed to 300°C, and the other operations were referred to Example 1 to obtain CeMn 0.24 -RT300 amorphous catalyst.

[0069] Embodiment 17

[0070] The calcination temperature in Example 2 was changed to 400°C, and the other operations were referred to Example 2 to obtain CeMn 0.24 -RT400 amorphous catalyst.

[0071] Embodiment 18

[0072] The calcination temperature in Example 2 was changed to 600°C, and the other operations were referred to Example 2 to obtain CeMn 0.24 -RT600 amorphous catalyst.

[0073] Comparative Example 1

[0074] In Example 1, Ce(NO3)3·6H2O was not added, and other operations were carried out in accordance with Example 1 to prepare a MnO2 catalyst.

[0075] The crystal structures of Examples 1-18 and Comparative Example 1 were characterized, and the XRD results are as follows: Figure 1 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 As shown, by adjusting the catalyst preparation parameters within the control range, the examples all tend to have an amorphous structure.

[0076] The nitrogen adsorption and desorption test results of Examples 1-18 and Comparative Example 1 are shown in Table 1. The examples all show a large specific surface area, and the transformation of the crystal phase is more conducive to the anchoring of the reaction molecules, promoting their adsorption and diffusion on the catalyst surface. Table 1 Catalyst nitrogen adsorption and desorption results

[0077] The electron microscopic results of Example 2 and Comparative Example 1 are shown in Figure 3 and Figure 4 , MnO2 has a rod-like structure, amorphous CeMn 0.24 The grain size is significantly reduced, showing uniform spherical particles and no regular lattice fringes are observed. This long-range disordered and short-range ordered structure will lead to more defects and more uniform active centers.

[0078] The VOCs catalytic activity of Examples 1-5 and Comparative Example 1 was evaluated, and the results are shown in Fig. 9 . At a total flow rate of 100 ml / min and an air velocity of 30000 ml·g -1 ·min -1 , chlorobenzene concentration 3000mg / m 3 Under the test conditions, CeMn 0.24 The catalyst can reach 100% conversion rate at 200℃, which is 60℃ lower than that of MnO2 catalyst.

[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a rare earth-manganese composite amorphous catalyst for VOCs catalysis, wherein the rare earth element is Ce, La, Pr or Nd; characterized in that: The following steps are involved: (1) dissolving a rare earth element precursor and Mn(CH3COO)2·4H2O in deionized water, stirring with a magnetic force until the solid is completely dissolved to form a mixed solution, and adjusting the pH of the solution to be in the range of 4.0 to 6.5 or 7.2 to 8.0; the molar ratio of the rare earth element precursor to Mn(CH3COO)2·4H2O is 0.12 to 0.60; (2) adding potassium permanganate solution to step (1), stirring for 30 min, transferring the obtained brown liquid into a hydrothermal reaction kettle, and subjecting the mixture to a hydrothermal reaction at 80-110° C. for 12-24 h; (3) washing, drying, calcining and grinding the black precipitate obtained in step (2) to obtain a composite amorphous catalyst; the calcination time is 3 to 5 hours and the calcination temperature is 300 to 600°C.

2. The method according to claim 1, wherein the concentration of Mn(CH3COO)2·4H2O in the mixed solution is 0.425 mol / L, and the concentration of potassium permanganate solution is 0.2-0.3 mol / L.

3. The method according to claim 1, wherein the rare earth element precursor added is any one of nitrate, acetate, and chlorate.

4. The method according to claim 1, characterized in that When acid is added to adjust pH, the acid is acetic acid, hydrochloric acid, or nitric acid. When alkali is added to adjust pH, the alkali is 0.1 mol / L NaOH solution.

5. The method according to claim 1, characterized in that The precipitate is washed alternately with anhydrous ethanol or deionized water for multiple times until it becomes neutral, the drying temperature is 90-110° C., and the drying time is 12-24 hours; after drying, the precipitate is calcined in an air atmosphere.

6. A rare earth-manganese composite amorphous catalyst prepared by the method according to any one of claims 1 to 5.

7. Use of the rare earth-manganese composite amorphous catalyst as claimed in claim 6 in catalytic oxidation of VOCs.

Citation Information

Patent Citations

  • Amorphous CexMnO2 material, and preparation method and application thereof

    CN110801829A

  • Preparation method and application of Ce-doped epsilon-MnO2 nano particles

    CN111389391A

  • Ce-Mn-based solid solution catalyst and preparation method and application thereof

    CN113262801A

  • Amorphous manganese oxide composite material as well as preparation method and application thereof

    CN115676896A

  • VOC removal catalyst and method for producing the same

    JP2021126599A